The Political Man and Contingent Valuation: Motives Do Count - Karine Nyborg (Statistics Norway, Research Department, 1996)
In addition to his role as a consumer pursuing his own interests, an individual may also regard himself as an ethical observer, judging matters from society's point of view. It is not clear which of these possibly conflicting roles respondents in contingent valuation studies take on. This leads to ambiguities in the interpretation of reported willingness to pay. I formalize this problem using a simple model of respondents' behaviour, based on the concept of subjective social welfare functions. The model may provide one explanation to several puzzling phenomena often found in contingent valuation studies; such as large discrepancies between willingness to pay and willingness to accept, frequent occurrence of "outliers" willing to pay extremely large amounts, and certain kinds of framing effects.
Keywords: A13; D11; D61; D62; H41; Q21; 330; Environmental valuation; social welfare judgements; non-unique preference orderings.